Development of a Web-Based E-Learning Platform for the Study of Ancient Iraqi Civilizations - N. Fawzi, Husam; A. Yousif, Suhad; Shakir Mahmood, Layth (Al-Nahrain Journal of Science, 2025)
E-learning has become widespread in the educational community, especially due to recent advances in information technology and communications and the integration of technology into our daily lives. Still, most major e-learning platforms are generalized and not tailored to a specific subject. In this paper, we address this issue by developing a prototype of a web-based e-learning platform specifically tailored for the study of ancient Iraqi civilizations. This will raise awareness about the major contributions of Iraq’s civilizations to the rest of the world, such as the invention of writing, urbanization, timekeeping, and farming techniques. The proposed platform leverages modern web technologies to provide an engaging and immersive learning experience to the students, and it offers a responsive design for cross-device displays. Key features for the teachers include managing civilizations and lessons, supporting multimedia files, managing a question bank, and a dynamic testing system for the students with real-time feedback for both students and teachers. This prototype represents a groundwork, as it is built with future scalability in mind, such as integrating artificial intelligence, virtual reality, and augmented reality, to enrich the study of Iraq’s civilizations.